Advances in high-voltage supercapacitors for energy storage systems: materials and electrolyte tailoring to implementation. Issue 3 (18th January 2023) - Lim, Jae Muk; Jang, Young Seok; Van T. Nguyen, Hoai; Kim, Jun Sub; Yoon, Yeoheung; Park, Byung Jun; Seo, Dong Han; Lee, Kyung-Koo; Han, Zhaojun; Ostrikov, Kostya (Ken); Doo, Seok Gwang
Abstract : Supercapacitor is a promising energy storage device for short term energy storage system (ESSs). This review, covers materials and electrolyte tailoring needed to achieve high V supercapacitor, essential for designing an efficient short term ESSs. Abstract : To achieve a zero-carbon-emission society, it is essential to increase the use of clean and renewable energy. Yet, renewable energy resources present constraints in terms of geographical locations and limited time intervals for energy generation. Therefore, there is a surging demand for developing high-performance energy storage systems (ESSs) to effectively store the energy during the peak time and use the energy during the trough period. To this end, supercapacitors hold great promise as short-term ESSs for rapid power recovery or frequency regulation to improve the quality and reliability of power supply. In particular, the electrical double layer capacitor (EDLC) which offers long and stable cycle retention, high power densities, and fast charge/discharge characteristics with a moderate operating voltage window, is a suitable candidate. Yet, for implementation of the EDLC in ESSs, further research effort is required in terms of increasing the operating voltage and energy densities while maintaining the long-term cycle stability and power densities which are desirable aspects for ESS operation. Here, we examine the advances in EDLC research to achieve a high operating voltage window along with high energy densities, covering from materials and electrolytes to long-term device perspectives for next-generation supercapacitor-based ESSs.